2020
DOI: 10.15644/asc54/3/1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Two Hyaluronic Acid Gel Products for the Treatment of Interdental Papillary Defects

Abstract: Objectives The aim was to investigate the efficacy of single injections of two different hyaluronic acid products, Flex Barrier and Revident, in reducing the size of black triangles to treat Nordland-Tarnow Class I and II recessions. Materials and Methods Forty adult patients were recruited with at least two upper and two lower interdental papilla defects in the front region between canine teeth. According to the Nordland-Tarnow classification of papillary defects, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Due to its multiple advantageous properties, HA is also broadly used in other areas of tissue regeneration, such as orthopedics to treat osteoarthritis and rheumatoid arthritis (24,25). Moreover, it is utilized in ophthalmology, dermatology (26), as well as in certain dental procedures (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its multiple advantageous properties, HA is also broadly used in other areas of tissue regeneration, such as orthopedics to treat osteoarthritis and rheumatoid arthritis (24,25). Moreover, it is utilized in ophthalmology, dermatology (26), as well as in certain dental procedures (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Both groups showed relapse in 1 week and 1 month although not till the initial level of papilla the results were slightly better in group 2. It was also established that the smaller the defect better is the outcome with both the groups (27).…”
Section: Papilla Regenerationmentioning
confidence: 97%
“…From 2016 till now, six studies on HA have been published including two RCTs, 12,14 two comparative studies, 19,20 and two case reports. 24,25 Black space reduction was noticed immediately after injection, 10 significant improvement after 3 months, 19,20 but less improvement was shown after 6 months.…”
Section: Hyaluronic Acid Injectionmentioning
confidence: 99%
“…Two studies administered HA using three step technique whereby each step consisted of 0.1 mL HA injection at mucogingival junction, attached gingiva, and 2 to 3mm from tip of papilla. 14 20 Alternatively, another study reported 0.1 mL HA injection at base of papilla and was repeated at 3 and 6 weeks. 19 Generally, there was a significant papillary reconstruction with better results observed in Class I Nordland 14 and thick gingiva.…”
Section: Hyaluronic Acid Injectionmentioning
confidence: 99%
See 1 more Smart Citation